Reliable data communication using post‐quantum encryption in Internet of Everything - Balaji, Ashwin; Dhurandher, Sanjay Kumar (International journal of communication systems, 2022)
Summary Internet of Everything (IoE) is one of the emerging technologies in the advancement of digital life and innovation. But the major issue that is to be addressed is the security concerns over such an environment, especially in end‐to‐end device communication. The proposed approach primarily focuses on reliable end‐to‐end device communication using post‐quantum location‐aware encryption, aiming to achieve confidentiality and integrity in an Internet of Everything environment. Even though the post‐quantum techniques have shown to be one of the evolving solutions for reliable data communication, but its robustness against the Man‐In‐The‐Middle and Sybil attacks is still a wide‐open subject and undiscovered. Numerous traditional encryption algorithms are now in use, while post‐quantum encryption is being studied and considered as a quantum‐safe substitute. The proposed approach also demonstrates a robust attack model which focuses on communication network threats like namely, Man‐In‐The‐Middle and Sybil attacks intending to evaluate the overall performance of the network by analyzing the performance parameters like, number of nodes in the network, message size, execution time, and memory consumption by the nodes and aiming to achieve an appreciable accuracy in an IoE environment. The proposed approach focuses on reliable end‐to‐end communication using post‐quantum location‐aware encryption, aiming confidentiality and integrity in an IoE environment. The approach also demonstrates a robust attack model which focuses on communication network threats namely, Man‐In‐The‐Middle and Sybil attacks intending to evaluate the overall performance of the network by analyzing the performance parameters like, number of nodes in the network, message size, execution time, and memory consumption by the nodes and aiming to achieve an appreciable accuracy.